PENGEMBANGAN PERSAMAAN PERPINDAHAN PANAS ALIRAN UDARA DALAM AIR - Achmad Fauzan (Jurnal Gamma, 2010)
For the calculation of direct contact heat exchanger between water and air bubble, it needformula of heat transfer. This research is dedicated for it. Attempt installation basically is a columnof water highly 1m which intemperature. Control. Air bubbles are discharged In this column. Byassuming those bubbles as ball with certain diameter the experiment was done. The result a Formulaof heat transfer coefficient with set of constant